Parliamentary elections in the srez of Berane in 1925 and 1927 - Virijević, Vladan A.; Deletić, Zdravko M. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
During the second half of the 20s in the last century political circumstances in Berane and its narrow gravitational area were known by constant rivalry between two civil political parties where the National Radical Party and the Yugoslav Democratic Party as well as the new Independent Democratic Party that was formed after the split of the Yugoslav Democratic Party, were the most influential ones within the Serbian national corps. Some new party lists – the Association of Peasants and the Yugoslav Muslim Organization appeared for the first time during the elections in 1925 and 1927 while they were not part of the organized elections in the first half of the 20s. Moreover, the electoral struggles were also characterized by the appearance of “factionary” party lists of candidates that were emphasized by certain local political leaders who were guided by their own ambitions, in spite of the orientation of the party headquarters especially among “democrats”, The common characteristics of the elections in 1925 and 1927 were that they took part in the environment which did not have the developed tradition of political organizing, and then it was considered as the undeveloped agricultural area without economic, financial subjects or cultural institutions that could influence the content of campaign and the results of elections more seriously. In the area of district political parties that were active in the country competed with each other, while the individuals, who did not live in this area nor were even born in this region, were often members of these lists and had mandates. Furthermore, there was the separation of voters and also different lists from the same party were presented several times. The followers of Muhammad had recognizable profiled candidates and lists but it can be proved that religious differences were not the obstacle for becoming a candidate in the parties as well as in their common lists. The results of the elections in 1925 left Berane and its surrounding without “its” Member of Parliament. Although Pavle Čubrović, the representative of the “dissident list” of the Democratic Party, won the most votes, the fact that most voters elected the radicals’ lists of candidates during the elections, decreased the importance of his result. However, two years later the result of the elections was completely different – the list of candidates of the Democratic Party won all three mandates for the Member of Parliament during the elections and therefore Čubrović became the Member of Parliament for the second time.